Innovation Of It Communications - Kadirova Shokhibonu Muhammadovna (Zien Journals, 2022)
The article described the Unified National Marketplace will be the only mechanism for the sale of domestically produced goods throughout the world through online access, and organizing online receipt of multicurrency payments, thus facilitating the costs associated with organizing trade in goods locally and abroad. One of the main points is the organization of receiving multi-currency payment and simplifying the difficulties associated with the export of products manufactured in the Republic of Uzbekistan, will also allow businesses and individuals to provide their goods to personal stores.
Keywords: multi-functional electronic trading platform; information flow; data flow; information flow objects